Co-inoculation of Debaryomyces hansenii and lactic acid bacteria: a strategy to improve the taste and odour profiles of dry sausages - Rongxin Wen; Yumeng Sui; Jiaqi Liu; Huiping Wang; Baohua Kong; Ligang Qin; Qian Chen (Food Science and Human Wellness)
The effects of the co-inoculation of Debaryomyces hansenii separately with 3 lactic acid bacteria (LAB), Lactobacillus sakei, Lactobacillus plantarum and Lactobacillus curvatus, on the taste and odour profiles of dry sausages were investigated. The co-inoculated sausages showed higher free amino acid and organic acid contents than the non-inoculated control and sausages inoculated with D. hansenii alone. Meanwhile, the sausages inoculated with D. hansenii + L. plantarum, D. hansenii + L. sakei and D. hansenii + L. curvatus had the highest contents of aldehydes, esters and alcohols, respectively. The results of electronic tongue, electronic nose and sensory evaluation demonstrated that compared with the sausage inoculated with D. hansenii, the sour taste and floral odour increased and the fatty odour decreased in the sausage inoculated with D. hansenii + L. sakei; this was more favourable for the development of a desirable flavour in sausages. Moreover, the partial least squares regression analysis indicated that 10 taste and 33 odour compounds were mainly responsible for the differences in the flavour profiles among the sausages. Overall, these findings contributed to a more comprehensive understanding of the formation of sensory characteristics in dry sausages co-inoculated with yeast and LAB.